Exploring the cultural awareness of students majoring in English: a case study - Andi Anto Patak; Sahril; Muhammad Basri Wello (Center for Humanities and Innovation Studies, 2018)
Cultural competence has become an important element in creating a positive academic atmosphere. This study is a case study on the case of Cross-Cultural Understanding course. The participants or research subjects of this study consisted of 48 (forty eight) diploma, 21 (twenty one) bachelor, 20 (twenty) master, and 8 (eight) doctorate program. This study found out that doctorate students are consistently perceived the cultural awareness. This study does not mean that the older the student the wiser their acceptance to different culture due to some of the diploma program show the highly perceived on cultural awareness. This study revealed that cultural awareness is reasonably allied to the level of education. The majority of diploma group are in a medium cultural awareness. Bachelor and master showed significantly that they are in the medium level of cultural awareness. This study recommends for further study to conduct a quantitative study to investigate the cultural awareness of the students before and after the course of Cross-Cultural Understanding and to examine the increase the students’ cultural awareness.